Attenuation of Hemodynamic Responses to Laryngoscopy and Tracheal Intubation: Propacetamol versus Lidocaine—A Randomized Clinical Trial - Ali Kord Valeshabad; Omid Nabavian; Keramat Nourijelyani; Hadi Kord; Hossein Vafainejad; Reza Kord Valeshabad; Ali Reza Feili; Mehdi Rezaei; Hamed Darabi; Mohammad Koohkan; Poorya Golbinimofrad; Samira Jafari (Anesthesiology Research and Practice)
The purpose of this study is to assess the effects of propacetamol on attenuating hemodynamic responses subsequent laryngoscopy and tracheal intubation compared to lidocaine. In this randomized clinical trial, 62 patients with the American Anesthesiologists Society (ASA) class I/II who required laryngoscopy and tracheal intubation for elective surgery were assigned to receive propacetamol 2 g/I.V./infusion (group P) or lidocaine 1.5 mg/kg (group L) prior to laryngoscopy. Systolic and diastolic blood pressures (SBP, DBP), mean arterial pressure (MAP), and heart rate (HR) were recorded at baseline, before laryngoscopy and within nine minutes after intubation. In both groups P and L, MAP increased after laryngoscopy and the changes were statistically significant (P<0.001). There were significant changes of HR in both groups after intubation (P<0.02), but the trend of changes was different between two groups (P<0.001). In group L, HR increased after intubation and its change was statistically significant within 9 minutes after intubation (P<0.001), while in group P, HR remained stable after intubation (P=0.8). Propacetamol 2 gr one hour prior intubation attenuates heart rate responses after laryngoscopy but is not effective to prevent acute alterations in blood pressure after intubation.